Evaluasi Usability Aplikasi Spotify Berbasis Mobile Menggunakan System Usability Scale (SUS) - Muhammad Hafidz; Aditya Triguna Wicaksana; Setyo Bagus Adi Nugroho; Zuhrul Anam; Dendy Kurniawan (CV. Denasya Smart Publisher, 2026)
Spotify is a mobile-based music streaming application that is widely used by the public to access digital entertainment in a practical manner. The high level of usage of this application requires ease of use (usability) so that users can operate the application comfortably and efficiently. Therefore, usability evaluation is needed to determine the extent to which the Spotify application is able to meet user needs. This study aims to evaluate the usability level of the mobile-based Spotify application using the System Usability Scale (SUS) method. The research was conducted using a descriptive quantitative approach by distributing a SUS questionnaire consisting of ten questions to 58 respondents who are Spotify application users. The data obtained was analyzed by calculating the SUS score of each respondent and the average usability score. The results showed that the mobile-based Spotify application obtained an average SUS score of 62.59, which is in the marginal category with a grade of C and an OK rating. These results indicate that the Spotify application is generally quite easy to use, but there are still several usability aspects that need to be improved. The System Usability Scale (SUS) method was used because it is able to provide quick, reliable usability measurements and is widely used in the evaluation of mobile-based applications. Thus, it can be concluded that the usability of the mobile-based Spotify application is quite good, but there are still aspects that need to be improved.